Parthenogenesis is self-destructive for scaled reptiles - Moreira, Matthew Owen (2021)
Parthenogenesis is rare in nature. With 39 described true parthenogens, scaled reptiles (Squamata) are the only vertebrates that evolved this reproductive strategy. Parthenogenesis is ecologically advantageous in the short term, but the young age and rarity of parthenogenetic species indicate it is less advantageous in the long term. This suggests parthenogenesis is self-destructive: it arises often but is lost due to increased extinction rates, high rates of reversal or both. However, this role of parthenogenesis as a self-destructive trait remains unknown. We used a phylogeny of Squamata (5388 species), tree metrics, null simulations and macroevolutionary scenarios of trait diversification to address the factors that best explain the rarity of parthenogenetic species. We show that parthenogenesis can be considered as self-destructive, with high extinction rates mainly responsible for its rarity in nature. Since these parthenogenetic species occur, this trait should be ecologically relevant in the short term.